Teachers' attitudes toward supervisory practices as related to certain variables - Ansay, Azucena A. (s.n.], 1970)
The objective of the study is to determine the attitudes of teachers toward supervisory practices in Laguna as related to certain variables. A five point attitude inventory was designed and developed to permit the assessment of the degree of teacher's attitudes toward each supervisory practice given in the inventory. The study aims to help the supervisor in gaining a deeper insight into the operation of his supervisory program. This study purported to help the supervisor determine how he could beter fill his own professional role, and how he could alleviate individual teachers' dissatisfactions and insecurities.